The Application of Collaboration System-Based Learning in Overcoming Syntactic Interference in the Abstracts of Teacher Professional Program Students - Niswa, Khairun; Srikandi, Cut Novita; Zuliana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
This study aims to explore the application of collaborative learning techniques as a strategy to overcome syntactic interference of Indonesian into English in the abstract writing of Teacher Professional Program (PPG) students at FKIP UMSU. Collaborative learning is learning that encourages learners to interact with each other, cooperate, and work together. The approach used was descriptive qualitative research method, involving collaboration techniques between students in focus discussion groups to improve the syntactic structure of the abstract. The research data were taken from 25 student abstracts, before and after the collaborative learning intervention. The analysis showed that collaborative learning significantly reduced syntactic interference such as the absence of to be, the use of inverted phrase patterns, and passive sentence structure errors. In addition, it was found that this approach increased students' linguistic awareness of the fundamental differences between Indonesian and English syntax. This research makes a real contribution to the development of more effective English teaching techniques for professional teacher education, as well as offering practical strategies for improving the academic quality of students in higher education. The implications of this research open up opportunities to expand the application of collaborative learning in other language teaching contexts.